Switching to darunavir/ritonavir monotherapy vs. triple-therapy on body fat redistribution and bone mass in HIV-infected adults: the Monarch randomized controlled trial. (March 2014) - Guaraldi, Giovanni; Zona, Stefano; Cossarizza, Andrea; Vernacotola, Luisa; Carli, Federica; Lattanzi, Antonella; Nardini, Giulia; Orlando, Gabriella; Garlassi, Elisa; Termini, Roberta; Garau, Marzia
Changes in body fat distribution and bone mass in HIV-infected patients may be associated with long-term use of nucleoside reverse transcriptase inhibitors (NRTIs). The Monarch trial recruited 30 patients receiving non-nucleoside reverse transcriptase inhibitor or protease inhibitor−based highly active antiretroviral therapy, with HIV RNA <40 copies/mL. Patients were randomized to either darunavir/ritonavir 800/100 mg once daily monotherapy or darunavir/ritonavir 800/100 mg once daily + two NRTIs. Bone mass, peripheral lipoatrophy and central fat accumulation were assessed using dual-energy X-ray absorptiometry scanning, supplemented by computed tomography scans. Median age was 43 years, 77% were men. Visceral adipose tissue remained stable from baseline to Week 48 in the whole group ( p  = 0.261) with no significant difference between arms ( p  = 0.56). There was a significant reduction in insulin resistance (HOMA-IR, p  = 0.013) over 48 weeks in the whole group, but not of body mass index ( p  = 0.24). In the darunavir/ritonavir monotherapy arm, there was a small but significant increase in both lumbar and femur bone mineral density at 48 weeks and was observed after correction for baseline values. The absolute change in lumbar bone mineral density at 48 weeks was more pronounced in the darunavir/ritonavir arm compared with the darunavir/ritonavir + 2NRTIs arm. In this study, discontinuing nucleoside analogues and switching to darunavir/ritonavir monotherapy was associated with a small but statistically significant increase in bone mineral density, but stable levels of limb fat and visceral adipose tissue.